2006
DOI: 10.1007/s10681-006-9272-7
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of Cry proteins in roots and border cells of transgenic cotton

Abstract: Transgenic cotton plants expressingCry1Ac and Cry2Ab, from the soil bacterium Bacillus thuringiensis (Bt), provide effective control of certain lepidopteran pests, however, little is known about the proteins below ground expression. We used ELISA to quantify in vitro expression of the Cry1Ac and Cry2Ab proteins in mucilage, root border cells and root tips in five transgenic cultivars of cotton compared to conventional cultivar Sicot 189. Expression of Cry proteins in roots and border cells of the transgenic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…However, Bt proteins, such as Cry1Ab and Cry1Ac, can be released into the soil from cotton residues, root exudates and pollen during growth and after harvest (Gupta and Watson, 2004;Knox et al, 2007). As the growing cultivation acreage of transgenic Bt cotton, the environmental impact monitoring after commercial release has attracted increasing attention from public and the scientific community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Bt proteins, such as Cry1Ab and Cry1Ac, can be released into the soil from cotton residues, root exudates and pollen during growth and after harvest (Gupta and Watson, 2004;Knox et al, 2007). As the growing cultivation acreage of transgenic Bt cotton, the environmental impact monitoring after commercial release has attracted increasing attention from public and the scientific community.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its promising effect on pest suppression, the total cultivation acreage of Bt cotton has expanded dramatically in northern China since 1997 (Huang and Pray, 2002). However, Bt proteins such as Cry1Ac and Cry1Ab produced in leaves, pollen and roots of Bt cotton can be introduced to soil through biomass incorporation and root exudates (Gupta and Watson, 2004;Knox et al, 2007;Li et al, 2012;Mina et al, 2008). Once released in soil, Bt toxin get adsorbed or bound on clay particles, humic components, or organic mineral complexes and in this way is protected against degradation by soil microorganisms (Tapp et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al (2006) showed new evidence that the Bt crystal proteins were mostly located in the cytoplasm and intercellular space of Bt transgenic cotton GK-12 cotyledon mesophyll cells, which provides indirectly evidence for the above intraradical damage mechanism. Knox et al (2007) used ELISA to quantify in vitro expression of the Cry1Ac and Cry2Ab proteins in mucilage, root border cells and root tips in five transgenic cultivars of cotton compared to conventional cultivar Sicot 189. Expression of Cry proteins in roots and border cells of the transgenic cotton cultivars was constitutive and at detectable levels, with Cry1Ac and Cry2Ab protein expression ranging from\20 to[100 pbb.…”
Section: Impact Mechanisms Of Gmps On Amfmentioning
confidence: 99%
“…Ground corn powder (Monsanto, Australia), previously used in published ELISA and bioassay studies [21,22], was found to produce a reliable standard over the range of 0.3 to 70 PPB (y= -12.7x 2 + 62.0x + 0.5, R 2 = 0.99, n=15). However, it was found to be susceptible to freeze/thawing, thus aliquots and dilutions were prepared fresh when required.…”
Section: Evaluation Of Seasonal Levels Of Cry1ac and Cry2ab In Field mentioning
confidence: 99%